Modeling soil erosion using a spatially distributed model in a karst catchment of northwest Guangxi, China. Issue 15 (5th August 2014) - Feng, Teng; Chen, Hongsong; Wang, Kelin; Zhang, Wei; Qi, Xiangkun
ABSTRACT Reliable assessment of the spatial distribution of soil erosion is important for making land management decisions, but it has not been thoroughly evaluated in karst geo‐environments. The objective of this study was to modify a physically based, spatially distributed erosion model, the revised Morgan, Morgan and Finney (RMMF) model, to estimate the superficial (as opposed to subsurface creep) soil erosion rates and their spatial patterns in a 1022 ha karst catchment in northwest Guangxi, China. Model parameters were calculated using local data in a raster geographic information system (GIS) framework. The cumulative runoff on each grid cell, as an input to the RMMF model for erosion computations, was computed using a combined flow algorithm that allowed for flow into multiple cells with a transfer grid considering infiltration and runoff seepage to the subsurface. The predicted spatial distributions of soil erosion rates were analyzed relative to land uses and slope zones. Results showed that the simulated effective runoff and annual soil erosion rates of hillslopes agreed well with the field observations and previous quantified redistribution rates with caesium‐137 (137Cs). The estimated average effective runoff and annual erosion rate on hillslopes of the study catchment were 18 mm and 0.27 Mg ha−1 yr−1 during 2006–2007. Human disturbances played an important role in accelerating soil erosion rates with the average values ranged from 0.1 to 3.02 Mg ha−1 yr−1 for different land uses. The study indicated that the modified model was effective to predict superficial soil erosion rates in karst regions and the spatial distribution results could provide useful information for developing local soil and water conservation plans. Copyright © 2014 John Wiley & Sons, Ltd.